Penanaman Nilai-Nilai Karakter bagi Santri di Pondok Pesantren Anwarul Ulum Desa Lintas Utara Kecamatan Keritang Kabupaten Indragiri Hilir Provinsi Riau - Sutrisno Sutrisno; Fuad Rahman; Musli Musli (Departement of Mathematics Education, 2023)
This research is a qualitative research using descriptive method which was conducted at the Anwarul Ulum Islamic Boarding School, Lintas Utara Village, Keritang District, Indragiri Hilir Regency, Riau Province. Data collection techniques are observation, interviews, and documentation. Data analysis techniques in this study include: data reduction, data presentation, and data verification. As well as checking the validity of the data is to use the triangulation technique. The findings from this study indicate that the cultivation of character values implemented at Anwarul Ulum Islamic Boarding School is through a boarding system, learning, exemplary, and habituation. While the obstacles that arise in the process of cultivating these character values are two, namely obstacles that come from within and obstacles from outside the Islamic Boarding School. The Islamic Boarding School's efforts to overcome internal factor barriers through the provision of sanctions and coaching are carried out by reciting recitation and calling students specifically while external factors are carried out by requiring all students to live in dormitories. Obstacles caused by the lack of awareness of the parents of the students were carried out through activities that were carried out together and through calling the parents of the students.